Peran Kepatuhan Syariah dalam Memediasi Pengaruh Kinerja Keuangan dan Good Corporate Governance Terhadap Pengungkapan Islamic Social Reporting pada Bank Umum Syariah di Indonesia - Idzhar Hanan Nurrohim; Gigih Aulia Hilmiawan; Anik Puji Handayani (CV. Ulil Albab Corp, 2026)
This study aims to analyze the effect of profitability and Good Corporate Governance (GCG) on Islamic Social Reporting (ISR) disclosure, with Sharia compliance acting as a mediating variable in Islamic Commercial Banks in Indonesia. The study employs a quantitative approach using secondary data obtained from annual reports of Islamic banks through documentation methods. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that profitability has a positive effect on ISR disclosure, while GCG does not significantly affect ISR disclosure. Furthermore, profitability and GCG are not sufficient to optimally explain variations in Sharia compliance. Sharia compliance is also not proven to mediate the relationship between profitability and GCG with ISR disclosure. These findings suggest that ISR disclosure in Islamic banking has not yet been fully driven by financial performance and corporate governance mechanisms through Sharia compliance. Therefore, strengthening other internal and external factors is necessary to improve Sharia compliance and the quality of ISR disclosure in Islamic banking in Indonesia.